2004
DOI: 10.1002/jgm.598
|View full text |Cite
|
Sign up to set email alerts
|

Purification of polyethylenimine polyplexes highlights the role of free polycations in gene transfer

Abstract: This study presents an efficient method to remove free PEI from PEI polyplexes by SEC. Our results from transfection experiments demonstrate that free PEI substantially contributes to efficient gene expression but also mediates toxic effects in a dose-dependent manner. Purified polyplexes without free PEI have to be applied at increased concentrations to achieve high transfection levels, but exhibit a greatly improved toxicity profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
392
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(426 citation statements)
references
References 24 publications
31
392
3
Order By: Relevance
“…To enable rational and focused design of siRNA delivery systems, detailed knowledge of the interaction between the vector polymers and the siRNA as well as between the polyplexes and the cells is necessary. PEI has been extensively characterized for DNA delivery [30][31][32]40]. For instance, it has been shown that high efficiency requires N/P ratios > 8 [30,40], while full condensation of the DNA is reached at N/P3-4 [30,31,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable rational and focused design of siRNA delivery systems, detailed knowledge of the interaction between the vector polymers and the siRNA as well as between the polyplexes and the cells is necessary. PEI has been extensively characterized for DNA delivery [30][31][32]40]. For instance, it has been shown that high efficiency requires N/P ratios > 8 [30,40], while full condensation of the DNA is reached at N/P3-4 [30,31,41].…”
Section: Discussionmentioning
confidence: 99%
“…PEI has been extensively characterized for DNA delivery [30][31][32]40]. For instance, it has been shown that high efficiency requires N/P ratios > 8 [30,40], while full condensation of the DNA is reached at N/P3-4 [30,31,41]. This indicates that a fraction of the vector has a role unrelated to condensation of DNA, and this fraction has been speculated to be free in solution or at least only weakly associated to the nucleic acid-containing polyplex.…”
Section: Discussionmentioning
confidence: 99%
“…43 Complexes had a final DNA concentration of 10 mg ml À1 . The presented data (Supplementary Table S3; Supplementary information) are means of three measurements, with each measurement averaging the data of 10 sub-runs.…”
Section: Polyplex Size and B-potential Measurementmentioning
confidence: 99%
“…Transfection efficiency was evaluated 24 h after treatment by measuring luciferase reporter gene expression using a luminometer (Lumat LB 9507; Berthold Technologies, Bad Wildbad, Germany) as previously described. 43 Two nanogram of recombinant luciferase (Promega, Mannheim, Germany) correspond to 10 7 light units. Protein concentration was determined using a BCA assay (Pierce, Rockford, IL, USA) with bovine serum albumin as a standard.…”
Section: In Vitro Transfection and Metabolic Activitymentioning
confidence: 99%
“…The transfection complex of linearized pCR3.1-CYP2B1 plasmid with PEI was generated at an N/P ratio (nitrogen in PEI/phosphate in DNA) of 6 in HBS (HEPES-buffered saline: 20 mM HEPES pH 7.1, 150 mM NaCl) at a final DNA concentration of 20 mg/ml. 13 Forty-eight hours after transfection, cells were selected with 0.5 mg geneticin per ml culture medium. To obtain subclones, the surviving cells were re-seeded in a 96-well plate at 1 cell/well after 2 weeks of geneticin selection.…”
Section: Cell Culturementioning
confidence: 99%